1987
DOI: 10.1002/bscb.19870960606
|View full text |Cite
|
Sign up to set email alerts
|

Simple Preparations of Some Hydantoins of Phenylalanine and α‐MePhe and Their Chiral Stability During N3‐Alkylation. A Route to the Synthesis of Chiral Amines

Abstract: A one s t e p q u a n t i t a t i v e route f o r 5-benzyl-5-methyl hydantoin is obt a i n e d by m e l t i n g a-MePhe with ureum. a t N-3 w i t h c o n s e r v a t i o n of the c h i r a l i t y a t C-5.Diastereomers r e s u l t i n g from asymmetric a l k y l groupings implanted a t N-3 can be s e p a r a t e d by c r y s t a l l i z a t i o n i n aqueous medium. y i e l d s w i t h B a ( 0 H ). T h i s allows t h e p r e p a r a t i o n of e n a n t i o m e r i c pure mines such l i k e 2-methylbutylanine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Various methodologies have been applied to the synthesis of 3,5-disubstituted hydantoins. A straightforward pathway is the alkylation/arylation [6][7][8][9][10] of the N-3 position of 5-or 5,5 0 -disubstituted hydantoins but most of the procedures describe the cyclisation of ureido derivatives of amino esters A, prepared by reaction with isocyanates (either in solution [11][12][13][14][15][16][17] or on solidsupport [18][19][20][21][22][23] ) (Method A, Scheme 1), phosgene, 24 or triphosgene. [25][26][27][28][29] We have recently demonstrated that mechanochemistry was successfully applied to the eco-friendly preparation of 5,5 0disubstituted hydantoins, 30 including the antiepileptic drug phenytoin (Phenytek®, Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Various methodologies have been applied to the synthesis of 3,5-disubstituted hydantoins. A straightforward pathway is the alkylation/arylation [6][7][8][9][10] of the N-3 position of 5-or 5,5 0 -disubstituted hydantoins but most of the procedures describe the cyclisation of ureido derivatives of amino esters A, prepared by reaction with isocyanates (either in solution [11][12][13][14][15][16][17] or on solidsupport [18][19][20][21][22][23] ) (Method A, Scheme 1), phosgene, 24 or triphosgene. [25][26][27][28][29] We have recently demonstrated that mechanochemistry was successfully applied to the eco-friendly preparation of 5,5 0disubstituted hydantoins, 30 including the antiepileptic drug phenytoin (Phenytek®, Fig.…”
Section: Introductionmentioning
confidence: 99%
“…General accesses to 5-mono- and 5,5-disubstituted hydantoins were provided early by Read synthesis and by Bucherer−Bergs method. The former comprised the reaction of amino acids and cyanate salts and the latter the condensation of carbonyl compounds with potassium cyanide and ammonium carbonate. , The condensation of α-dicarbonyl compounds with ureas represented another classical methodology that involved a step similar to the benzilic acid rearrangement. , …”
Section: Introductionmentioning
confidence: 99%